Dr. Demento : covered in punk [compact disc]. - Dr. Demento; Shatner, William; Vivino, Floyd; Schneider, Fred (Frederick W.), 1951-; Kochalka, James; Nobunny; Green, Colleen (Musician); Quintron; Miss Pussycat; Merrill, Andy; West, Adam, 1928-2017; Jett, Joan; et al. (Caf Muzeck, 2018)
An eclectic mix of artists from the world of classic and contemporary punk/indie/alt-rock have assembled, along with special guest stars from film, TV, and more, to pay homage to radio icon Dr. Demento. Over 30 different, never before released, all-new 'punk' cover versions of 'mad music and crazy comedy' songs famously heard on the airwaves of the legendary Dr Demento Show have been intermixed with 'wild card' tracks showcasing some incredible, newly 'demented' versions of punk-rock classics!